Triggering Consumer Interest: The Roles of Word of Mouth, Social Media Marketing, and Servicescape - Meirisa, Putri; Aisyah Azhar Adam; Parhusip, Austin Alexander (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study aims to determine and examine the impact of word-of-mouth, social media marketing and servicescape partially and simultaneously on Purchase Interest in Cols N Brew in Medan City. This research uses numerous straight relapse examination based on SPSS adaptation 25 investigation. The factual examination utilized in this investigate is Legitimacy and Unwavering quality Test, classical presumption test, different straight relapse examination, and theory testing. The population in this research is visitors to Cold N Brew Coffee, and the sample that cannot be known uses the Zikmund formula with a total of 100 respondents who visited Cold N Brew Coffee. The hypothesis used is that word of mouth, social media marketing, servicescape have a noteworthy impact on Consumer Purchase Interest. The results of this study are intended to help with the management of Cold N Brew Coffee in Medan City, in developing strategies to improve social media marketing and servicescape so as consumer buying interest.